Concepts of P Drug Selection (Nepal Journal of Epidemiology, 2013)
Personal (P) drug selection is an important part of the pharmacology teaching and learning session. Most of the textbooks that are commonly followed by the medical schools of Nepal merely tell about the concepts of P drug selection. Most of the time it is found that student cannot follow the concepts of P drug. Most of the literature that is available is in the international level, like international journals, guide to good prescription, teachers guide to good prescription etc. At the national level very few references are available. The activity of P drug selection can reduce the chances of irrational prescribing that is common problem in developing country like Nepal. Some of the important concepts regarding P Drug selection like it is a personal drug for a doctor and it is not for a patient, P drug is selected for a disease and not for a particular patient is also has been emphasized in this paper.DOI: http://dx.doi.org/10.3126/nje.v3i1.8280 Nepal Journal of Epidemiology 2013;3 (1): 226-229